2020
DOI: 10.1073/pnas.1920143117
|View full text |Cite
|
Sign up to set email alerts
|

The type IV pilin PilA couples surface attachment and cell-cycle initiation in Caulobacter crescentus

Abstract: Understanding how bacteria colonize surfaces and regulate cell-cycle progression in response to cellular adhesion is of fundamental importance. Here, we use transposon sequencing in conjunction with fluorescence resonance energy transfer (FRET) microscopy to uncover the molecular mechanism for how surface sensing drives cell-cycle initiation in Caulobacter crescentus. We identify the type IV pilin protein PilA as the primary signaling input that couples surface contact to cell-cycle initiation via the second m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…It was first discovered in Gluconacetobacter xylinus about 30years ago, as a positive allosteric regulator of cellulose synthase ( Ross et al, 1987 ). Subsequent studies have revealed that c-di-GMP regulates a variety of important cellular processes, including biofilm formation, motility, virulence, cell differentiation, cell cycle and mechanical sensing ( Tischler and Camilli, 2004 ; Kulesekara et al, 2006 ; Hengge, 2009 ; Boehm et al, 2010 ; Romling et al, 2013 ; Tschowri et al, 2014 ; Lori et al, 2015 ; Hug et al, 2017 ; Xu et al, 2019 ; Del Medico et al, 2020 ; Snyder et al, 2020 ). Such regulations may take place at the transcriptional, post-transcriptional, or post-translational levels by interacting with different types of effectors ( Romling et al, 2013 ; Chou and Galperin, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was first discovered in Gluconacetobacter xylinus about 30years ago, as a positive allosteric regulator of cellulose synthase ( Ross et al, 1987 ). Subsequent studies have revealed that c-di-GMP regulates a variety of important cellular processes, including biofilm formation, motility, virulence, cell differentiation, cell cycle and mechanical sensing ( Tischler and Camilli, 2004 ; Kulesekara et al, 2006 ; Hengge, 2009 ; Boehm et al, 2010 ; Romling et al, 2013 ; Tschowri et al, 2014 ; Lori et al, 2015 ; Hug et al, 2017 ; Xu et al, 2019 ; Del Medico et al, 2020 ; Snyder et al, 2020 ). Such regulations may take place at the transcriptional, post-transcriptional, or post-translational levels by interacting with different types of effectors ( Romling et al, 2013 ; Chou and Galperin, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One factor is that unphosphorylated DivK allosterically stimulates the kinase activity of PleC ( 26 ). Second, PleC signaling activity is regulated by pilus retraction upon surface contact ( 27 ). In this model, pilus retraction leads to the accumulation of PilA monomers in the periplasm that interacts and regulates PleC activity ( 27 ).…”
mentioning
confidence: 99%
“…However, a Cu stress-inducible aTSS was detected on its antisense strand. The PilA protein was recently shown to couple mechanical cell-surface contact with initiation of the cell cycle [ 122 ]. Expression of pilA is regulated by the cell-cycle regulator CtrA [ 123 ]; nonetheless, non-canonical factors governing its expression seem to be present.…”
Section: Resultsmentioning
confidence: 99%